Words Review Method: Peningkatan Keterampilan Mendengarkan (Listening) Mata Pelajaran Bahasa Inggris pada Siswa SMA Negeri Sugihwaras - Fitriani (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2021)
This study aims to improve listening skills for students of SMA Negeri 1 Sugihwaras through the application of review words method. This study is based on the low interest of learners towards listening. Students think that the learning delivered by educators and the methods used are boring and do not vary. This study uses experimental methods by giving treatment or action to learners through a strategy of listening, repeating, saying, in listening learning using a series of observation sheets. The results showed that the method of listening, reworking Review Words Method, said, as one of the efforts to improve the listening power is very effective and provide a significant improvement of listening skills for students.